The Syntactic Complexity of Noun Phrases in Second Language Students’ Writing - Clara Ofosua Frempong; Stella Akosua Kayi; Sitsofe Ganu (Linguistics Initiative, 2023)
Investigations on learners' writing have multiplied over the recent decades, but writings created by students of institutions of education are still mostly unstudied. This research looks into how noun phrases (NPs) were used in writings created by students at Ghanaian colleges of education (CoEs). Lu's (2010) three metrics for measuring overall NP complexity for text—a length-based metric of NP complexity, mean length of clause (MLC), and two specific NP complexity metrics—number of complex nominals per clause (CN/C) and number of complex nominals per T-Unit (CN/T)—were chosen and applied to a total of 318 texts written by Levels 100, 200, and 300 students from three colleges of education in Ghana. The results from the one-way ANOVA and its post hoc analysis showed a significant difference between Levels 100 and 300 students as well as between Levels 200 and 300 students in their use of complex noun phrases. Overall, Level 300 students significantly used more complex NPs than students in the other levels. It is recommended that in further studies, lexico-grammatical features such as relative clauses, prepositional phrases, and nominal clauses, should be analysed to assess complexity since academic language is a multifaceted entity which may be researched in various fields like SLA, applied linguistics, and language testing.